2014
DOI: 10.18052/www.scipress.com/ilns.14.77
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Production of Alkaline Proteases from Agro Byproducts Using a Novel <i>Trichoderma viridiae</i> Strain VPG 12, Isolated from Agro Soil

Abstract: In recent years, there has been a phenomenal increase in the use of alkaline proteases as industrial catalysts. The aim of this work was to isolate potent fungal strain from the agricultural field of Gulbarga region of India, for the production of alkaline protease by utilizing the agricultural by products viz, red and green gram and Bengal gram as substrate under submerged fermentation process. Optimization of fermentation process parameters such as substrate (Red gram husk, green gram husk and Bengal gram hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This situation suggested a feasible harvest (enzyme) at about 96 h (on day 4) of fermentation, similar to the findings published elsewhere (Abubakar and Oloyede, 2013;Costa et al, 2021;Maftukhah and Abdullah, 2018;Okoye et al, 2013). The incubation period, however, would depend on a number of factors, such as the availability/level of nutrients, fermentation environment, nature of fermenting organisms and the physiological conditions influencing the (fermentation) process (Patil and Dayanand, 2006;Shivasharanappa et al, 2014).…”
Section: Enzyme Production Ammonium Sulfate Precipitation Profile And...mentioning
confidence: 99%
“…This situation suggested a feasible harvest (enzyme) at about 96 h (on day 4) of fermentation, similar to the findings published elsewhere (Abubakar and Oloyede, 2013;Costa et al, 2021;Maftukhah and Abdullah, 2018;Okoye et al, 2013). The incubation period, however, would depend on a number of factors, such as the availability/level of nutrients, fermentation environment, nature of fermenting organisms and the physiological conditions influencing the (fermentation) process (Patil and Dayanand, 2006;Shivasharanappa et al, 2014).…”
Section: Enzyme Production Ammonium Sulfate Precipitation Profile And...mentioning
confidence: 99%
“… 11 reported maximum production of protease (9550 U/g biomass) by Bacillus species in green gram substrate. However, Shivasharanappa et al 12 reported lower production of protease in green gram husk as compared to red gram and Bengal gram husk. A similar finding was reported by Chmimata et al .…”
Section: Introductionmentioning
confidence: 98%
“…Extracellular microbial alkaline proteases are commercially important enzymes used extensively in several industries such as in the detergent, food, pharmaceutical, chemical, leather, silk, and waste treatment [1]. A large proportion of commercially important alkaline proteases is derived from the strains of Bacillus [2][3][4].…”
Section: Introductionmentioning
confidence: 99%